Novel Variant of the Androgen Receptor Gene in a Patient With Complete Androgen Insensitivity Syndrome and Polyorchidism - Konrade, Ilze; Zavorikina, Julija; Fridvalde, Aija; Rots, Dmitrijs; Kalere, Ieva; Strumfa, Ilze; Dambrova, Maija; Gailite, Linda (Frontiers in Endocrinology, 2019)
Introduction: Complete androgen insensitivity (CAIS) in 65-95 % cases is caused by pathogenic allelic variants (mutations) in the gene encoding androgen receptor (AR gene) and is characterized by female phenotype development with a male karyotype (46, XY). Patients are usually diagnosed during puberty and undergo gonadectomy due to increased testicular germ cell tumour risk. Only a few outcomes have been reported in older individuals with postponed gonadectomy. Case presentation: A 48-year-old CAIS patient presented with polyorchidism without gonadal malignancies. Genetic testing identified a novel allelic variant in the AR gene (c.2141T>G (p.Phe805Cys)) causing the clinical symptoms. Conclusion: We have described a unique patient with CAIS and polyorchidism without malignancies in her late 40’s bearing a novel likely pathogenic variant in the AR gene.